Climate change, transformative adaptation options, multiscale polycentric governance, and rural welfare in the Oum Er Rbia Basin, Morocco: empirical evaluation with policy implications - Saleth, Rathinasamy Maria; Amarasinghe, Upali A.; Amarnath, Giriraj; Ait El Mekki, Abdelkader; Seelanatha, Kaushika; Brouziyne, Youssef (International Water Management Institute, 2025)
This study examines how multiscale polycentric governance (MPG) can enhance the rural welfare impacts of three transformative adaptation options (TAOs) in Morocco, using an impact pathways approach. The framework linked 22 MPG elements and 30 impact transmission domains to three TAOs—conversion to high-value tree crops, contract farming/public–private partnerships, and drip irrigation modernization— and rural welfare through a system of 30 recursive equations. The model was estimated using stakeholder perception data (on a scale of 1–10) from 178 respondents in the Oum Er Rbia River basin via simultaneous regression techniques.